Prevention of HIV-1 TAT Protein-Induced Peripheral Neuropathy and Mitochondrial Disruption by the Antimuscarinic Pirenzepine - Han, May Madi; Frizzi, Katie E.; Ellis, Ronald J.; Calcutt, Nigel A.; Fields, Jerel Adam (Frontiers in Neurology, 2021)
HIV-associated distal sensory polyneuropathy (HIV-DSP) affects about one third of people with HIV and is characterized by distal degeneration of axons. The pathogenesis of HIV-DSP is not known and there is currently no FDA-approved treatment. HIV trans-activator of transcription (TAT) is associated with mitochondrial dysfunction and neurotoxicity in the brain and may play a role in the pathogenesis of HIV-DSP. In the present study, we measured indices of peripheral neuropathy in the doxycycline (DOX)-inducible HIV-TAT (iTAT) transgenic mouse and investigated the therapeutic efficacy of a selective muscarinic subtype-1 receptor (M1R) antagonist, pirenzepine (PZ). PZ was selected as we have previously shown that it prevents and/or reverses indices of peripheral neuropathy in multiple disease models. DOX alone induced weight loss, tactile allodynia and paw thermal hypoalgesia in normal C57Bl/6J mice. Conduction velocity of large motor fibers, density of small sensory nerve fibers in the cornea and expression of mitochondria-associated proteins in sciatic nerve were unaffected by DOX in normal mice, whereas these parameters were disrupted when DOX was given to iTAT mice to induce TAT expression. Daily injection of PZ (10 mg/kg s.c.) prevented all of the disorders associated with TAT expression. These studies demonstrate that TAT expression disrupts mitochondria and induces indices of sensory and motor peripheral neuropathy and that M1R antagonism may be a viable treatment for HIV-DSP. However, some indices of neuropathy in the DOX-inducible TAT transgenic mouse model can be ascribed to DOX treatment rather than TAT expression and data obtained from animal models in which gene expression is modified by DOX should be accompanied by appropriate controls and treated with due caution.